Memahami kejahatan akuntansi di indonesia - Sudrajat Martadinata (Imanensi: Jurnal Ekonomi, Manajemen, dan Akuntansi Islam, 2019)
Abstrak Tujuan penelitian ini untuk memahami kejahatan akuntansi yang terjadi di Indonesia, menurut mahasiswa program studi akuntansi Universitas Teknologi Sumbawa. Penelitian ini dalam jenis kualitatif dengan pendekatan fenomenologi, melalui beberapa tahapan analisa yakni: noema, epoche, noesis, intentional analysis, dan eidetic reduction. Kesimpulan dari penelitian ini bahwa di dalam memahami kejahatan akuntansi di Indonesia meurut mahasiswa akuntansi UTS sangat bergantung kepada dua faktor penting: 1) Ilmu akuntansi, 2) Moral manusia. Abstract The objective of this research was to construe the meaning of accountancy crime that happened in Indonesia, based on the thought of students of accountancy program of Sumbawa University of Technology. The research was qualitative with phenomenology approach, through some steps of analysis; noema, epoche, noesis, intentional analysis and eidetic reduction. The conclusion of this research showed that the mean plethora of accountancy crime cases which happened in Indonesia strongly depends on two important factors: 1) science of accountancy, 2) human’s moral.